2015
DOI: 10.1007/s00232-015-9779-8
|View full text |Cite
|
Sign up to set email alerts
|

L-Type Ca2+ Channels and SK Channels in Mouse Embryonic Stem Cells and Their Contribution to Cell Proliferation

Abstract: Mouse embryonic stem cells (mESCs) are capable of both self-renewal and multilineage differentiation; thus, they can be expanded in vivo or in vitro and differentiated to produce different cell types. Despite their biological and medical interest, many physiological properties of undifferentiated mESCs, such as ion channel function, are not fully understood. Ion channels are thought to be involved in cell proliferation and differentiation. The aim of this study was to characterize functional ion channels in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The corresponding SOCE channels are characterized by a nearly linear I / V curve and relatively low selectivity for calcium. It has been shown that drug targeting to calcium channels results in significant alterations of electrophysiological signals ( Vegara-Meseguer et al, 2015 ; Ryazantseva et al, 2017 ). To gain a deeper insight into the mechanism of drug targeting, it is important to discriminate between currents maintained by CRAC and TRPC channels.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding SOCE channels are characterized by a nearly linear I / V curve and relatively low selectivity for calcium. It has been shown that drug targeting to calcium channels results in significant alterations of electrophysiological signals ( Vegara-Meseguer et al, 2015 ; Ryazantseva et al, 2017 ). To gain a deeper insight into the mechanism of drug targeting, it is important to discriminate between currents maintained by CRAC and TRPC channels.…”
Section: Resultsmentioning
confidence: 99%
“…54 L-VGCCs have been demonstrated to regulate the proliferation of mouse ESCs (mESCs). 55 In addition, neural differentiation of mESCs is also strongly enhanced by L-VGCCs. 56,57 Experiments performed by Lepski indicates that L-VGCCs-mediated maturation of NSCs depends on enhanced intracellular cAMP levels.…”
Section: L-vg CC S and Emb Ryoni C S Tem Cell Smentioning
confidence: 99%
“…Huang et al carried out experiments on human ESC lines H7 and H9, indicating that these might be voltage‐insensitive cells, as depolarization‐induced Ca 2+ entry by a high K + solution did not change the intracellular free Ca 2+ concentration . L‐VGCCs have been demonstrated to regulate the proliferation of mouse ESCs (mESCs) . In addition, neural differentiation of mESCs is also strongly enhanced by L‐VGCCs .…”
Section: L‐vgccs and Embryonic Stem Cellsmentioning
confidence: 99%
“…Acquisition of electrophysiological features is a prominent manifestation of the differentiation of cells into neural and muscular lineage. However, pluripotent human stem cells (hESCs and induced pluripotent stem cells) functionally express specialized ion channels [33,34] which play important roles in the regulation of cell proliferation [as reviewed in [35,36]]. The expression analysis of ion channels in hESCs at the transcriptomics level has revealed approximately 100 voltage-gated ion channel genes, ten transcripts of which were significantly expressed [33].…”
Section: Ion Channels and Transportersmentioning
confidence: 99%